Implementasi Project Based Learning Dengan Pendekatan STEM Untuk Meningkatkan Kreativitas Berpikir Santri Pada Materi Termodinamika (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2025)
This study was conducted to determine how the effect of the implementation of the Project Based Learning (PjBL) model with the STEM approach on improving students' creative thinking skills on the material of the law of thermodynamics, with data collection techniques through pretest, posttest and questionnaire. The STEM approach is believed to be able to stimulate students to be more creative by integrating science, engineering, mathematics, and engineering in the learning process. The sampling technique used was Purposive Sampling, the sample amounted to 30 people who were students of Pondok Pesantren Modern Assa'adah Serang Banten. The analysis method used in this research is Quantitative Data Analysis. The results showed that there was an effect of the PjBL model with the STEM approach on improving the creative thinking skills of students on the material of the law of thermodynamics. The results of the posttest analysis obtained a p-value = 0.002. This shows that the p-value (sig)